NW / Zadie Smith. - Smith, Zadie (Hamish Hamilton, 2012)
Hobbes, Smith, Bentham, Locke and Russell. Five identical blocks make up the Caldwell housing estate in North West London. Caldwell kids Leah, Natalie, Felix and Nathan have all moved on. They occupy separate worlds in an atomized city. Then one afternoon a stranger comes to Leah's door, forcing her out of her isolation.